Evaluating Family Bundle Birthing Care to Improve Self-Efficacy and Reduce Maternal Anxiety During Pregnancy - Eniyati Eniyati; Fatimah Dewi Anggraeni; Sujono Riyadi; Muhammad Farid (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Pregnancy-related anxiety can affect both the experience and length of labor. Self-efficacy, defined as an individual’s belief in their ability to perform the behaviors required to achieve desired outcomes, plays a vital role in managing this anxiety. The Family Bundle Birthing Care (FBBC) approach, which actively involves the mother and her family especially the husband is believed to help lower anxiety levels and strengthen the pregnant woman’s self-efficacy. This study aims to assess the effect of the FBBC approach on reducing anxiety and enhancing self-efficacy among pregnant women. Methods: A quasi-experimental design was employed with intervention and control groups, each consisting of 50 pregnant women. Data was collected using the childbirth education (W-DEQ-A), (W-DEQ-B), childbirth self-efficacy (CBSEI), and birth confidence (BCSQ) questionnaires to assess anxiety and self-efficacy. Data analysis was conducted using the fisher exact test and independent t-tests. Results: The results indicated that the intervention group had significantly lower average scores on the W-DEQ-A and W-DEQ-B, and higher scores on the CBSEI and BCSQ questionnaires compared to the control group. The differences were statistically significant, with p-values of 0.001, 0.01, 0.02, and 0.01, respectively, suggesting that the family-based antenatal education program was effective in reducing anxiety and enhancing self-efficacy among pregnant women. Conclusion: The FBBC program proved effective in reducing anxiety and enhancing self-efficacy in pregnant women. This approach could serve as an alternative method to improve mental preparedness and psychological support for expectant mothers as they approach labor.